Perceived supplier opportunism in outsourcing relationships in emerging economies. Issue 7 (29th September 2020) - Skowronski, Keith; Benton, W. C.; Hill, James A.
Abstract: While opportunism has been a focus of transaction cost economics, perceived opportunism, where one party is perceived to be acting opportunistically when there is no opportunistic intent, can also lead to increased transaction costs in an exchange. In this study, consistent with forms of opportunism observed in our context of manufacturing outsourcing, we examine two different forms of perceived opportunism—perceived poaching and shirking. As narratives of the hidden costs of outsourcing discuss concerns of suppliers in emerging economies engaging in poaching and shirking, we examine if the level of economic development where a supplier operates affects perceptions of supplier poaching and shirking and also examine if the supplier's competitive priorities moderate those perceptions. To empirically test these relationships, we combine archival data of location characteristics with a dyadic primary dataset that captures perceived supplier opportunism, self‐reported supplier opportunism, and other relationship characteristics. Our findings illustrate that perceived opportunism and opportunism are distinct constructs and that more observable forms of opportunism (i.e., shirking) affect perceived opportunism more than less observable forms of opportunism (i.e., poaching). We also find that, in existing relationships, manufacturers in advanced economies perceive poaching to be more strongly related to the level of economic development where a supplier operates than shirking. Finally, we find that while a cost focus can mitigate perceptions of poaching, an innovation focus exacerbates them. Overall, our study illustrates the challenges that innovation‐focused suppliers in emerging economies face in regards to competing with suppliers in advanced economies. Abstract : Author Video